Development of fire model source terms and effects in the Hazard Prediction and Assessment Capability (HPAC) atmospheric transport and dispersion code - Jonathan M. Vogel; Roger Lucheta; Brendan Zinn; Jimmie Trigg (Atmospheric Environment: X, 2022)
This paper describes a model which has been developed to represent the input of the products of combustion of large fires into the atmosphere, for subsequent calculation of the transport and dispersion by atmospheric processes. The objective was to have a model suitable for rapid implementation to support the needs of emergency responders. Consequently, the model characterizes the sources by a small number of parameters, which then define the rest of the model in terms of quantity and rate of release of products of combustion.There are two fundamental situations modeled – a hydrocarbon pool fire, and a building fire. The hydrocarbon pool fire is characterized by the area and mass, while the various forms of building fires are reduced to two: wooden buildings and steel-framed buildings, with further discrimination being made by area and duration of the fire. The building fires are assumed to be driven primarily by cellulosic materials, with the amount of such material being normalized to the floor area with parameters taken from the literature.A certain number of toxic contaminants, with levels as suggested by the firefighting literature, are provided in these models. The analyst can amend these levels, or ignore them, as desired.The models developed have been incorporated into the Defense Threat Reduction Agency (DTRA) Hazard Prediction and Capability (HPAC) code. This code breaks down the hazard prediction process into three components: 1) Generation of a source term describing the introduction of the contaminant to the atmosphere; 2) Transport, dispersion, and deposition of the contaminants by atmospheric processes, and; 3) Computation of the effects of the contaminant, usually at the surface. Source term generation modules includes such things as biological and nuclear warfare, and toxic industrial chemicals (TIC). The present work adds a fire module to the mix.